mHealth versus face-to-face: study protocol for a randomized trial to test a gender-focused intervention for young African American women at risk for HIV in North Carolina - Felicia A. Browne; Wendee M. Wechsberg; Paul N. Kizakevich; William A. Zule; Courtney P. Bonner; Ashton N. Madison; Brittni N. Howard; Leslie B. Turner (BMC, 2018)
Abstract Background Disparities in the prevalence of HIV persist in the southern United States, and young African American women have a disproportionate burden of HIV as compared with young women of other racial/ethnic backgrounds. As a result, engaging young African American women in the HIV care continuum through HIV testing is imperative. This study is designed to reach this key population at risk for HIV. The study seeks to test the efficacy of two formats of a gender-focused, evidence-based, HIV-risk reduction intervention-the Young Women's CoOp (YWC)-relative to HIV counseling and testing (HCT) among young African American women between the ages of 18 and 25 who use substances and have not recently been tested for HIV. Methods Using a seek-and-test framework, this three-arm cross-over randomized trial is being conducted in three county health departments in North Carolina. Each county is assigned to one of three study arms in each cycle: in-person (face-to-face) YWC, mobile Health (mHealth) YWC, or HCT. At study enrollment, participants complete a risk behavior survey via audio computer-assisted self-interview, and drug, alcohol, and pregnancy screening tests, and are then referred to HIV, gonorrhea, and chlamydia testing through their respective health departments. Participants in either of the YWC arms are asked to return approximately 1 week later to either begin the first of two in-person individual intervention sessions or to pick up the mHealth intervention preloaded on a tablet after a brief introduction to using the app. Participants in all arms are asked to return for a 6-month follow-up and 12-month follow-up, and repeat the survey and biological testing from baseline. Discussion The findings from this study will demonstrate which delivery format (mHealth or face-to-face) is efficacious in reducing substance use and sexual risk behaviors. If found to be efficacious, the intervention has potential for wider dissemination and reach. Trial registration ClinicalTrials.gov: NCT02965014. Registered November 16, 2016.